Decades of Recovery From Sheep Grazing Reveal No Effects on Plant Diversity Patterns Within Icelandic Tundra Landscapes - Mörsdorf, Martin A.; Ravolainen, Virve T.; Yoccoz, Nigel G.; Thórhallsdóttir, Thóra Ellen; Jónsdóttir, Ingibjörg Svala (Frontiers in Ecology and Evolution, 2021)
Tundra plant communities are often shaped by topography. Contrasting wind exposure, slopes of different inclination and landforms of different curvature affect habitat conditions and shape plant diversity patterns. The majority of tundra is also grazed by ungulates, which may alter topographically induced plant diversity patterns, but such effects may depend on the spatial scales of assessments. Here we ask whether topographically induced patterns of within (alpha) and between (beta) plant community diversity are different in contrasting grazing regimes. We studied plant communities within tundra landscapes that were located in the North and Northwest of Iceland. Half of the studied landscapes were grazed by sheep, whereas the other half was currently un-grazed and recovering for several decades (up to 60 years). Alpha and beta diversity were assessed on explicitly defined, nested spatial scales, which were determined by topographical units. Although we contrasted currently grazed vegetation to vegetation that witnessed several decades of grazing recovery, we found no statistically significant differences in plant diversity patterns. We relate these findings to the low resilience of our study system towards grazing disturbances, which has important implications for management practices in the tundra. Alpha and beta diversity patterns were associated with small scale units of contrasting landform curvature and intermediate scale units of contrasting elevations under both grazing regimes, but not with large scale contrasts in slope exposure. These findings highlight the importance of using different spatial grain sizes of assessment. Ecosystem resilience and the spatial scales of assessments are therefore crucial determinants for our understanding of landscape diversity patterns.